2020
DOI: 10.1021/acs.cgd.0c00353
|View full text |Cite
|
Sign up to set email alerts
|

How Charged Amino Acids Regulate Nucleation of Biomimetic Hydroxyapatite Nanoparticles on the Surface of Collagen Mimetic Peptides: Molecular Dynamics and Free Energy Investigations

Abstract: Biomineralization is the concept of biologically controlled or induced aggregations of salt ions, which is one of the most widely spread phenomena in nature. The formation of bones is one of the prototypical biomineralization processes which involves the association of calcium and phosphate ions to generate the apatite crystals on collagen fibers. In this work, the nucleation mechanism was investigated from a microscopic point of view using molecular dynamics (MD) and metadynamics simulations. Compared to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 91 publications
0
35
0
Order By: Relevance
“…39 The electrostatic interaction between the positively charged argnine residue and PO4 3ion could regulate the HA nucleation process by the arginine residue of collagen. 40 The distribution of postively and negatively charged groups at the CaP cluster surface could be correlated with the zeta potential experiments in the following subsection. Zeta potential was used to estimate the average surface electronegativities.…”
Section: Aggregation Of Cap Clusters In Aqueous and Sbf Solutionsmentioning
confidence: 90%
See 1 more Smart Citation
“…39 The electrostatic interaction between the positively charged argnine residue and PO4 3ion could regulate the HA nucleation process by the arginine residue of collagen. 40 The distribution of postively and negatively charged groups at the CaP cluster surface could be correlated with the zeta potential experiments in the following subsection. Zeta potential was used to estimate the average surface electronegativities.…”
Section: Aggregation Of Cap Clusters In Aqueous and Sbf Solutionsmentioning
confidence: 90%
“…The regulation of nucleation process of CaP by the charged amino acids of collagen surface was demonstrated by CHARMM27 based MD study in solution. [38][39][40] Neutral amino acids of collagen such as glycine and hydroxyproline residues, whose carboxylate groups were also found to be freely accessible to the Ca 2+ ions based on generalized AMBER force field. 41 The interactions between lysine and HA (100) surface was ascribed to the dominant electrostatic interaction in Ca-O ionic bonding, followed by hydrogen bonding between Cε-H/amine-H and phosphate-O.…”
Section: Introductionmentioning
confidence: 99%
“…If, during characterization, such changes are detected, consider changing the location of the functional handle (e.g., middle vs end of peptide) or the functional handle identity. Use of molecular dynamic simulations to evaluate the location that will have the least impact on peptide properties may also be of value. Difficulties visualizing sample . There are a number of reasons sample visualization may be challenging, including poor labeling, low sample concentration, and assembled peptide structure size.…”
Section: Methods 4: Peptide Structure Visualization Within a Hydrogelmentioning
confidence: 99%
“…If the cells were pretreated with chlorpromazine (clathrin-pathway inhibitor) ( Shi et al, 2017 ) or NaN 3 (ATP inhibitor), ( Ryan et al, 2015 ) the uptake of HAp were significantly prohibited, indicating clathrin-mediated and ATP-dependent endocytosis for HAp nanoparticles. The physicochemical properties of HAp as well as its interactions with proteins (such as collagen) or substrates have also been extensively studied at atomic level ( Cheng et al, 2017 ; Wang et al, 2018b ; Wang et al, 2018c ; Liu et al, 2018 ; Xie et al, 2018 ; Gu et al, 2019 ; Xue et al, 2019 ; Liu et al, 2020 ; Ma et al, 2020 ; Tan et al, 2020 ; Wang et al, 2020 ). However, only a few studies have reported the clathrin-mediated adhesion and endocytosis of HAp, ( Shi et al, 2017 ; Shi et al, 2018 ; Huang et al, 2020 ) while the molecular details remain elusive.…”
Section: Introductionmentioning
confidence: 99%